Southern-led development finance : solutions from the global South - Barrowclough, Diana; Gallagher, Kevin, 1968-; Kozul-Wright, Richard, 1959- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
"Southern-Led Development Finance examines some of the innovative new south-south financial arrangements and institutions that have emerged in recent years, as countries from the Global South seek new ways to transform their economies and to shield themselves from global economic turbulence. A few decades ago it would have been difficult to predict the rapid emergence of the trillion dollar holdings of today's southern-owned development banks, infrastructure funds, foreign exchange reserve funds and Sovereign Wealth Funds. The book argues that southern-led development finance plays a significant part in a wider search for new and different paths towards more inclusive, equitable and sustainable patterns of investment, trade and growth. This book brings together insights from theory and from practice, incorporating the voices of bankers, policymakers and practitioners alongside those of international academic researchers. It covers the largest and most high profile new initiatives stemming from Asia; some tried and tested examples in Latin America; experiences in Africa; and also the role advanced economies are contributing to the mix. Whilst the book tends towards the view that Southern-led initiatives could potentially change the global financial landscape profoundly, it also discusses the variation in the success of these initiatives, and recognises that ensuring finance works truly for development requires more than just the technical availability of funds. As governments and businesses frustrated by the traditional North-dominated mechanisms and international financial system seek new approaches to investment, trade and finance, this book is a timely contribution to the debate. It will be of interest to practitioners, policy makers, researchers and students working on development finance"--
OCLC-licensed vendor bibliographic record.
Keywords: Economic development -- Developing countries; Economic development -- Finance; Development banks -- Developing countries; Finance -- Developing countries; Developing countries -- Foreign economic relations